Crafting Sustainable Futures. The Value of the Service Designer in Activating Meaningful Social Innovation from within Textile Artisan Communities. (28th July 2017) - Mazzarella, Francesco; Mitchell, Val; Escobar-Tello, Carolina
Abstract: In order to tackle complex sustainability challenges, top-down one-size-fits-all services and strategies do not always effectively address the diverse needs of local communities. It is increasingly recognised that multi-disciplinary stakeholders need to draw on their locally situated knowledge and cooperate towards achieving a social aim. With this in mind, and moving beyond the designer's 'parachuting' into projects that do not grow or develop, this paper explores how the service designer can contribute to activate meaningful routes for the transition of textile artisan communities towards sustainable futures. This paper proposes a service design framework for better understanding local contexts, making sense of visions for the future and reframing them into meaningful actionable realities. For the purpose of this paper, the theory is here presented through its application to a community of Nottingham lace artisans, chosen as unit of analysis for this participatory case study research.